2000
DOI: 10.1080/105846000198468
|View full text |Cite
|
Sign up to set email alerts
|

Race and Public Deliberation

Abstract: Although deliberation has a central place in democratic theory, scholars know little about how it actually works. Most deliberative theorists emphasize the many good consequences of deliberation. By contrast, Mansbridge suggests that deliberation in certain circumstances may exacerbate conflict. Scholarship on racial politics suggests that each hypothesis is complicated by implicitly racial language. Using a quasiexperiment, we contrast the rhetoric in two town meetings about school desegregation: a segregated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
116
0
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 184 publications
(124 citation statements)
references
References 29 publications
1
116
0
3
Order By: Relevance
“…10 In early studies concerning the deliberative impact on empathy, Mendelberg (2002), in line with theories of motivated reasoning, suggested that linguistic intergroup bias -the privileging of arguments by members your own group at the expense of out-groups -is likely to undercut the ability of individuals to empathize. In a follow up piece, Mendelberg and Oleske (2000) found that discussion did not produce greater tolerance for opposing views nor mitigated conflict. This work suffered from a methodological bias, reliant upon participants' self-assessment for measures of empathy.…”
Section: Meso-changes: Social Learning Polarization and Consensusmentioning
confidence: 99%
“…10 In early studies concerning the deliberative impact on empathy, Mendelberg (2002), in line with theories of motivated reasoning, suggested that linguistic intergroup bias -the privileging of arguments by members your own group at the expense of out-groups -is likely to undercut the ability of individuals to empathize. In a follow up piece, Mendelberg and Oleske (2000) found that discussion did not produce greater tolerance for opposing views nor mitigated conflict. This work suffered from a methodological bias, reliant upon participants' self-assessment for measures of empathy.…”
Section: Meso-changes: Social Learning Polarization and Consensusmentioning
confidence: 99%
“…Many critics reasonably worry that deliberation in practice could be perverse, magnifying political inequality if the people who select into deliberation are already privileged (Sanders 1997). Other critics are concerned that racial dynamics produce less than representative deliberative groups, with ensuing negative outcomes for underrepresented minorities (Mendelberg and Oleske 2000). Some sources of variation in willingness to deliberate may be normatively benign, and others that are less benign might be ameliorated in practice if we understood how they worked.…”
Section: Beyond Skepticism and Optimism About Deliberative Participationmentioning
confidence: 99%
“…Many scholars (Eliasoph 1998;Hibbing and TheissMorse 2002;Mendelberg and Oleske 2000;Mutz 2002;Posner 2003 ;Sanders 1997;Sunstein 2009) worry that pushing deliberation on reluctant citizens, beyond wasting time and resources, will cause actual harm by leading to even greater frustration with and aversion toward politics. Even some scholars who are highly sympathetic to deliberative democracy echo such concerns (e.g., Mansbridge 1980) under some circumstances.…”
Section: A Note On the Consequences Of Deliberationmentioning
confidence: 99%
“…In a study of New Jersey town meetings held in both segregated and integrated environments, for example, Mendelberg and Oleske (2000) found that language used by whites in segregated meetings had the veneer of being universal, well-reasoned, focused on the common good, and supportive of the community consensus, but on closer inspection, such language also seemed to advance a narrow group interest (that is, the interests of privileged Whites). At integrated meetings, such language was decoded by many non-Whites as racist and an obstruction to the larger public good.…”
Section: Group Deliberation and Language At Public Meetingsmentioning
confidence: 99%